RETRACTED: The Influence Of Physical Work Environment, Communication, Motivation And Career Development On Employee Performance At Pt. Erlangga Karya Gemilang Jakarta - Ita Yuliana Sari; Herry Krisnandi; Kumba Digdowiseiso (Journal of Social Science)
This study aims to analyze the relationship between the influence of physical work environment, communication, motivation and career development on the performance of employees of PT. Erlangga Karya Gemilang Jakarta. The sample in this study were 146 employees of PT. Erlangga Karya Gemilang Jakarta, the sampling method used is Simple Random Sampling. The sampling technique in this study is to take samples from one population and use a questionnaire. The analytical method used in this research is descriptive analysis method through the analysis of perception levels and using the help of the IBM SPSS 23 program. The linear regression equation answers the influence of physical work environment, communication, motivation and career development on employee performance is Y = 0.407X1 + 0.614X2 + 0.463X3 + 0.569X4 and the Physical Work Environment, Communication, Motivation and Career Development for Employee Performance is Y1 = 0.479X1 + 0.484X2 + 0.559X3 + 0.565X4 + 0.210Y. The results showed that the influence of physical work environment, communication, motivation and career development directly had a positive and real effect on employee performance.